1994
DOI: 10.1111/j.1752-7325.1994.tb01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Total Tooth Loss in the United States; Longitudinal Analysis of National Data

Abstract: The NHANES I Epidemiologic Follow-up Study (NHEFS) of 1982-84 collected longitudinal data from 10,523 individuals initially seen during the first National Health and Nutrition Examination Survey (NHANES I) of 1971-75. Among this additional data was information on the incidence of total tooth loss during the 10 years between the surveys, which could then be added to NHANES I data to identify risk factors. In this analysis, a series of bivariate analyses were carried out, followed by logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
152
3
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 13 publications
19
152
3
4
Order By: Relevance
“…It is well known that the risk of tooth loss increases as the number of PT decreases 4,14,31,33) . We believe greater awareness of this fact among the general public would encourage a change in behavior with regard to regularly visiting their dentist, which should help prevent further tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the risk of tooth loss increases as the number of PT decreases 4,14,31,33) . We believe greater awareness of this fact among the general public would encourage a change in behavior with regard to regularly visiting their dentist, which should help prevent further tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…The notable bad habits among the study population were smoking 6.0%, beetle nut chewing 4.0% and snuffing 3.0%. Eklund and Burtn reported there were associations between total tooth loss and low income, education, perceived poor oral health, smoking and negative health behavior 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents. Some study revealed that Dental and oral health are affected by diet and certain aspects of lifestyle [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations